Pengaruh Peraga Garis Bilangan Terhadap Pemahaman Siswa SD Tentang Operasi Pengurangan Bilangan Bulat Negatif - Wini Megayani; Oyon Haki Pranata; Aan Kusdiana (EduBasic Journal: Jurnal Pendidikan Dasar, 2019)
Mathematics is one of the subjects in school that trains students to think logically and systematically. Therefore, it is important for students to understand all material presented.  Unfortunately, based on the preliminary study results in, it showed that in learning mathematics especially in operation of negative integer’s subtraction is still not well-understood since the difficulty of distinguishing minus signs and negative signs. This is due to the lack of use of teaching aids related to the materials. To solve the problem, researcher used the number line media assisted with puppet to deliver concept of concrete object going back and forth on a number board. This research tried to measure the effect of the number line media on students understanding of the operation of negative integer’s subtraction. This pre-experimental with one-group pretest-posttest design research found that students’ understanding of the operation of negative integer’s subtraction before using the number line media was an average value of 57.0, while after using the number line media showed an average value of 80.4. Based on the result of the t-test, the significance value of students pretest and  posttest result was 0,000. If compared to 0,000 0,005 the H0 is rejected and Ha is accepted. It can be concluded that the number line media has a significant influence on students understanding of the operation of negative integer’s subtraction.